The metabolic resistance of Nilaparvata lugens to chlorpyrifos is mainly driven by the carboxylesterase CarE17 - Lu, Kai; Li, Yimin; Xiao, Tianxiang; Sun, Zhongxiang (Ecotoxicology and environmental safety, 2022)
The involvement of carboxylesterases (CarEs) in resistance to chlorpyrifos has been confirmed by the synergism analysis in Nilaparvata lugens. However, the function of specific CarE gene in chlorpyrifos resistance and the transcriptional regulatory mechanism are obscure. Herein, the expression patterns of 29 CarE genes in the susceptible and chlorpyrifos-resistant strains were analyzed. Among them, CarE3, CarE17 and CarE19 were overexpressed in the resistant strain, and knockdown of either CarE gene by RNA interference significantly increased the susceptibility to chlorpyrifos. Remarkably, knockdown of CarE17 reduced the enzymatic activity of CarE by 88.63 % and showed a much greater effect on increasing chlorpyrifos toxicity than silencing other two CarE genes. Overexpression of CarE17 in Drosophila melanogaster decreased the toxicity of chlorpyrifos to transgenic fruit flies. Furthermore, the region between − 205 to + 256 of CarE17 promoter sequence showed the highest promoter activity, and 16 transcription factors (TFs) were predicted from this region. Among these TFs, Lim1β and C15 were overexpressed in the resistant strain. Knockdown of either TF resulted in reduced CarE17 expression and a decrease in resistance of N. lugens to chlorpyrifos. These results indicate that the constitutive overexpression of Lim1β and C15 induces CarE17 expression thus conferring chlorpyrifos resistance in N. lugens. •Three CarE genes were involved in chlorpyrifos resistance of N. lugens.•Metabolic resistance of N. lugens to chlorpyrifos is extremely attributed to CarE17.•Potential binding sites for homeobox TFs were predicted from CarE17 promoter.•Lim1β and C15 induces CarE17 expression thus increasing chlorpyrifos resistance.